2018
DOI: 10.1177/2325967118808778
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Using a Bone–Patellar Tendon–Bone Graft With and Without a Ligament Augmentation Device: A 25-Year Follow-up of a Prospective Randomized Controlled Trial

Abstract: Background:Various grafts and ligament augmentation devices (LADs) have been used in the search for optimal reconstruction of the anterior cruciate ligament (ACL).Purpose:To compare 25-year follow-up results after ACL reconstruction using a bone–patellar tendon–bone (BPTB) graft with or without the Kennedy LAD.Study Design:Randomized controlled trial; Level of evidence, 1.Methods:One hundred patients undergoing ACL reconstruction between 1991 and 1993 were randomized into 2 groups: reconstruction using a BPTB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…We further screened these studies and excluded unmatched group dividing studies, studies with no available or relative data, studies with incomplete data, studies with short-term follow-up and other studies needed to be excluded according to the search strategy. Finally, 30 studies were included [ 12 , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [75] , [76] , [77] , [78] , [79] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , 92 ].
Figure 1 Summary of search process with PRISMA.
…”
Section: Resultsmentioning
confidence: 99%
“…We further screened these studies and excluded unmatched group dividing studies, studies with no available or relative data, studies with incomplete data, studies with short-term follow-up and other studies needed to be excluded according to the search strategy. Finally, 30 studies were included [ 12 , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [75] , [76] , [77] , [78] , [79] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , 92 ].
Figure 1 Summary of search process with PRISMA.
…”
Section: Resultsmentioning
confidence: 99%
“…25,44 Previous studies have assessed the incidence of OA after ACL reconstruction using HT and BPTB at 10- to 15-year follow-up and noted an incidence of OA between 21% and 51%. 9,21,25 Outcomes of ACL reconstruction at minimum 20-year follow-up have been assessed by several studies 7,8,10,35,37,38,40,42 ; however, these studies used BPTB grafts or a combined intra- and extra-articular reconstruction, and studies investigating the long-term outcomes of HT graft ACL reconstruction are lacking. One study assessed the long-term (20-year) outcomes of HT graft ACL reconstruction using femoral screw fixation, 35 but no studies have investigated the 20-year outcomes of HT graft reconstruction with femoral cortical button fixation.…”
mentioning
confidence: 99%
“…From the search of the three online databases, a total of 748 studies were identified, and 426 eligible studies were screened after duplicates were excluded. Two studies were of the same patients with different follow-up times [ 23 , 24 ], and we included the most recent study. Seven studies [ 24 30 ] met the predetermined inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were of the same patients with different follow-up times [ 23 , 24 ], and we included the most recent study. Seven studies [ 24 30 ] met the predetermined inclusion criteria. All studies compared bone-patellar tendon-bone (BPTB) grafts with artificial grafts, and no studies evaluating other autografts were identified.…”
Section: Resultsmentioning
confidence: 99%